The Relationship Between Knowledge and Attitude with Clean and Healthy Lifestyle Behavior of Owner of Batak Restaurant In Tigaraja Market, Tigaraja Village, Girsang Sipangan Bolon District, Simalungun Regency - Jumadiah Wardati; Tresia Melianna Simanjuntak (International Journal of Public Health Excellence (IJPHE), 2023)
Clean and healthy living behavior in Indonesia is currently still low, this is related to various health problems or the spread of environmental-based diseases which are epidemiologically high in Indonesia. This research was conducted to determine the relationship between knowledge and attitudes with clean and healthy living behavior of typical Batak restaurant owners in Tigaraja Market, Tigaraja Village, Girsang Sipangan Bolon District, Simalungun Regency in 2022. This type of research is descriptive with a population of all typical Batak restaurant owners in Pasar Tiga. King with a sample of 30 total sampling technique. The results of this study obtained that the majority of respondents were aged 41 — 60 years, namely 18 people (60%) while the minority had ages > 60 years, namely 5 people (16%). The majority of the respondent's last education was high school, namely 11 people (36.7%) while the minority with the last education was elementary school, namely 5 people (16.7%) and tertiary education, namely 5 people (16.7%). The majority have good knowledge, namely as many as 15 people (50%) while the minority have less knowledge, namely as many as 5 people (16.7 % ). The majority had an attitude of agreeing as many as 16 people (53.3%) while the minority had an attitude that did not agree as many as 14 people (46.7%). The majority had good behavior as many as 17 people (56.7 % ) while the minority had bad behavior as many as 13 people (43.3%). The results of the chi-sguare test variable knowledge p value 0.009, attitude variable p value 0.031, it can be concluded that knowledge and attitudes have a relationship with clean and healthy living behavior of typical Batak restaurant owners in the Tiga Raja market, Tiga Raja Village, Girsang Sipangan Bolon District, Simalungun Regency 2022.